2018
DOI: 10.1177/0269881118799953
|View full text |Cite
|
Sign up to set email alerts
|

The dose-dependent psychomotor effects of intravenous delta-9-tetrahydrocannabinol (Δ9-THC) in humans

Abstract: Background: Binding studies have demonstrated that levels of the cannabinoid receptor type-1 are highest in the basal ganglia and cerebellum, two areas critical for motor control. However, no studies have systematically examined the dose-related effects of intravenous delta-9-tetrahydrocannabinol, the primary cannabinoid receptor type-1 partial agonist in cannabis, on broad domains of psychomotor function in humans. Aims: Therefore, three domains of psychomotor function were assessed in former cannabis users (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 100 publications
1
12
0
Order By: Relevance
“…Previous studies have reported improvements in both hands after strength training in healthy elderly people [38] and music training in children [39], focusing more particularly on hand dexterity. Nevertheless, different outcomes for both hands have also been observed in studies determining motor function following sleep deprivation among medical personnel [40] and after an intravenous delta-9-tetrahydrocannabinol challenge [41]. Inconsistent with our results, these two latter studies reported statistically significant alterations for the non-dominant hand, but not for the dominant hand.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have reported improvements in both hands after strength training in healthy elderly people [38] and music training in children [39], focusing more particularly on hand dexterity. Nevertheless, different outcomes for both hands have also been observed in studies determining motor function following sleep deprivation among medical personnel [40] and after an intravenous delta-9-tetrahydrocannabinol challenge [41]. Inconsistent with our results, these two latter studies reported statistically significant alterations for the non-dominant hand, but not for the dominant hand.…”
Section: Discussionsupporting
confidence: 83%
“…The timing of the blood samples was selected to maximize the likelihood of detecting changes in drug-induced gene expression. A battery of subjective and cognitive assessments was administered to capture the effects and safety of THC 23,25,26 (See Methods).…”
Section: Single Cell Rna-seq Profiling Identifies Cell Types and Sub-mentioning
confidence: 99%
“…A battery of subjective and cognitive assessments were administered to capture the effects and safety of THC. 18, 20, 21 We profiled the four PBMC samples (two pre-THC and two post-THC) on the 10X Genomics platform. 22 Quality control processing yielded a total of 15,973 cells and 21,430 genes for analyses ( Figure 1a ).…”
Section: Mainmentioning
confidence: 99%